The Implementation of Genre-Based Approach in Writing Narrative Text of Eighth Grade Students at SMP 19 Palu - Trivani Trivani; Budi Budi; Maghfira Maghfira (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
The Implementation of Genre-Based Approach in Writing Narrative Text aims to examine the effectiveness of the Genre-Based Approach (GBA) in enhancing narrative text writing skills among eighth-grade students at SMP Negeri 19 Palu. The research method employed is quasi-experimental with two groups: an experimental group applying GBA and a control group that did not receive this treatment. Data were collected through pre-test and post-test assessments to measure students' writing skill improvements. The findings indicate that the average score of the experimental group increased from 54.55 to 73.62, while the control group improved from 40.07 to 64.15. In addition to score improvements, the quality of students' writing also showed enhancement in aspects of content, organization, vocabulary, language use, and mechanics. This study provides evidence that the Genre-Based Approach can significantly improve students' writing skills.